Joint proprietorship and business partnership (‘inan) in Islamic law: an analysis of the defining criteria - Sadique, Muhammad Abdurrahman (Edusage Network, 2019)
While the principal focus with regard to application Islamic modes of partnership in the fields of commerce and finance happen to be on contractual partnership or shirkah al ‘aqd, Islamic law has also laid down the fundamental principles and rules pertaining to joint proprietorship, where an asset, right, usufruct etc. is held in common by two or more parties. Islamic law categorizes the joint proprietary relationship as a type of partnership, based on the factor of joint sharing found therein, albeit limited to ownership rights, as against joint investment and profit sharing found in business partnership. Detailed guidelines are provided in Islamic legal sources on the nature, conditions, rights and liabilities resulting from such joint proprietorship. The current paper attempts to study the key features of joint ownership/proprietorship as discussed in the major works of Islamic law, while providing a summary of shirkah al-‘inan, the type of business partnership that allows free investment of capital for profit sharing, by way of comparison.